African Historical Past: A Paradox of Global Reality in the Twenty-First Century - Akanmidu, Paul Ilesanmi (ASPENSI in Bandung, Indonesia, 2015)
ABSTRACT: Africa continent has under-gone various historical phases, like other continents of the world. It will, therefore, tantamount to mono-causer argument to justify the condition of the continent based on the impact of a phase without giving reference to other phases, as it appears to be the central argument of the proponents of dependency theory. However, Africa was once a centre of civilization. In the context of reality, it is more or less a paradox of history in the twenty-first century. Africaâs glory is benighted and riddles in the expression of rhetoric and illusion. The continent is imploded and ravaged with multidimensional problems. Some scholars attributed the phenomenon to the Atlantic slave trade and colonialism, while others saw it as a matter of destiny. This paper uses the lens of history to give a panoramic evaluation of its socio-political and economic situations in the pre-colonial, colonial, and post-colonial eras. The study argues that even though the present situation of Africa continent leans on its past, slave trade, and colonialism can no longer be used exclusively as viable evidence for its stagnation and backwardness in the world history. It argues that Africaâs problems are with Africans, and there would be no change in the situation if Africans continue with the strategy of external aids, assistance, technology transfer from Europe and Americas. There is the need for structural overhauling of African systems, most especially the enemies of moral, political, educational, and economy.KEY WORDS: Africa, paradox of history, slave trade, colonialism, military, corruption, strategy of external aids, and structural overhauling of African systems.About the Author: Paul Ilesanmi Akanmidu, Ph.D. is a Lecturer at the Department of History & International Studies, Akungba-Akoko, Ondo State in Africa. For academic interests, the author is able to be contacted via e-mail at: paulakanmidu@gmail.comHow to cite this article? Akanmidu, Paul Ilesanmi. (2015). âAfrican Historical Past: A Paradox of Global Reality in the Twenty-First Centuryâ in TAWARIKH: International Journal for Historical Studies, Vol.7(1) October, pp.1-14. Bandung, Indonesia: Minda Masagi Press, ISSN 2085-0980.Chronicle of the article: Accepted (February 28, 2015); Revised (April 21, 2015); and Published (October 28, 2015).